A semi-solid lithium-ion battery

By using semi-solid design and coating process to prepare conductive layers in lithium-ion batteries, the problem of difficulty in lithium-ion batteries is solved, and the problem of high magnification, high energy density and high safety performance is achieved, and higher battery performance and safety are achieved.

CN114709468BActive Publication Date: 2025-04-01ZHENGXIONG (CHANGSHU) POWER SYST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210069057.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-20
Publication Date
2025-04-01
Estimated Expiration
2042-01-20

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are difficult to have high magnification, high energy density and high safety performance.

Method used

The semi-solid lithium-ion battery design is adopted, including a positive electrode structure and a negative electrode structure. The negative electrode structure consists of a current collector, an negative electrode active material layer and a solid electrolyte layer. The surface of the current collector is covered with a conductive layer. The conductive layer is prepared through a coating process, and a multi-layer structure is set on the negative electrode active material layer.

Benefits of technology

It improves the battery's rate performance and safety performance while maintaining high energy density, solving the contradiction between high magnification and high safety of traditional lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114709468B_ABST
    Figure CN114709468B_ABST
Patent Text Reader

Abstract

The present application provides a semi-solid lithium ion battery, the battery comprising a positive electrode structure and a negative electrode structure, the negative electrode structure comprising a current collector and a negative electrode active material layer and a solid electrolyte layer arranged on the current collector, and the solid electrolyte layer is arranged on the negative electrode active material layer, the surface of the current collector is covered with a conductive layer, and the conductive layer is obtained by applying a conductive slurry to the surface of the current collector through a carbon coating process. The present application carbonizes the current collector in the negative electrode structure through a carbon coating process, and arranges multiple layers of negative electrode active material layers in the negative electrode structure, thereby avoiding the problem of the negative electrode active material layer and the current collector layer easily falling off due to frequent large current charging and discharging, and improving the rate performance of the battery, thereby achieving a better solution to the contradictory problem of rate battery safety and energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a semi-solid lithium-ion battery. Background Art

[0002] Today's world is experiencing two revolutions. One is the new energy revolution under the background of "carbon neutrality". The other is the revolution of digitalization and intelligence. In the future, everything from various engineering vehicles and industrial robots to private cars, home appliances and furniture, and wearable devices will be fully digitalized and intelligent, and eventually all things will be connected. Both of the above revolutions are closely related to a thriving field at present - lithium-ion batteries.

[0003] Under the guidance of the "dual carbon" policy, the electric vehicle industry is developing rapidly, and lithium-ion batteries with high energy density and fast charging and discharging speed are becoming more and more popular in the market. Various engineering equipment, furniture and home appliances, wearable devices, and power tools also put forward higher requirements for the energy density and rate performance of lithium-ion batteries.

[0004] Traditional lithium-ion batteries have high energy density and good rate capability, but it is often difficult to achieve high safety at the same time. Solid-state lithium batteries have high energy density and good safety, but poor rate capability. This has become a factor limiting the application of lithium-ion batteries.

[0005] Therefore, it is urgent to propose a new lithium-ion battery to solve the above problems. Summary of the invention

[0006] In order to solve one or more of the above-mentioned technical problems existing in the prior art, an embodiment of the present application provides a semi-solid lithium-ion battery to solve the problem that the lithium-ion battery in the prior art cannot have high rate, high energy density and high safety performance at the same time.

[0007] In order to achieve the above-mentioned purpose, the technical solution adopted by this application to solve its technical problems is:

[0008] The present application provides a semi-solid lithium-ion battery, which includes a positive electrode structure and a negative electrode structure, wherein the negative electrode structure includes a current collector and a negative electrode active material layer and a solid electrolyte layer arranged on the current collector, and the solid electrolyte layer is arranged on the negative electrode active material layer, and the surface of the current collector is covered with a conductive layer, and the conductive layer is obtained by applying a conductive slurry to the surface of the current collector through a carbon coating process.

[0009] Furthermore, the preparation process of the conductive paste includes:

[0010] Dissolving graphene powder and a dispersant in a preset solvent to obtain a graphene dispersion, wherein the graphene comprises at least two different particle sizes; preferably, the preset solvent comprises water;

[0011] A preset amount of binder is added to the graphene dispersion and then mixed evenly in a high-speed stirrer to obtain the conductive slurry.

[0012] Furthermore, the graphene includes graphene with a first particle size and graphene with a second particle size, the D50 of the graphene with the first particle size is 150-200nm, and the D50 of the graphene with the second particle size is 40-60nm.

[0013] Furthermore, the mass ratio of the graphene of the first particle size to the graphene of the second particle size is [20-30]:[70-80].

[0014] Furthermore, the mass ratios of the graphene, the dispersant and the binder in the conductive paste are 4-9wt%, 0.5-1wt% and 1-2wt%, respectively. Preferably, the sum of the mass of the graphene, the dispersant and the binder accounts for (10-12)wt% of the total mass of the conductive paste.

[0015] Furthermore, the single-layer coating density of the conductive paste coated on the surface of the current collector is 1.11 to 1.95 g / ㎡.

[0016] Furthermore, the thickness of the conductive layer is 1.5-2.5 μm

[0017] Further, the thickness of the negative electrode active material layer is 5-300 μm, preferably, the thickness of the negative electrode active material layer is 10-200 μm, and further preferably, the thickness of the negative electrode active material layer is 20-50 μm.

[0018] Furthermore, the negative electrode active material layer includes at least a first negative electrode active material layer close to one side of the current collector and a second negative electrode active material layer close to the solid electrolyte layer, and the binding force of the binder contained in the first negative electrode active material layer is stronger than the binding force of the binder contained in the second negative electrode active material layer.

[0019] Furthermore, the solid electrolyte layer includes LLZO or LLTO.

[0020] Furthermore, the negative electrode active material layer includes a binder, a conductive agent and a negative electrode active material.

[0021] Furthermore, the negative electrode active material includes any one of graphite, graphene or carbon nanotube (CNT) or a combination of at least two thereof.

[0022] Preferably, the negative electrode active material is artificial graphite.

[0023] Furthermore, the negative electrode active material may be doped with one or more conductive materials that provide an electron conduction path and / or at least one polymer binder material that improves the structural integrity of the negative electrode.

[0024] Furthermore, the conductive agent includes one or a combination of at least two of carbon-based materials, powdered nickel or other metal particles, or conductive polymers.

[0025] Preferably, the carbon-based material includes one or a combination of at least two of carbon black, graphite, super-P, acetylene black, carbon fiber and nanotube, and graphene.

[0026] Preferably, the conductive polymer includes one or a combination of at least two of polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate.

[0027] Furthermore, the solid electrolyte layer includes a solid electrolyte material, and the solid electrolyte material includes one or more polymer components, oxide particles, sulfide particles, halide particles, borate particles, nitride particles or hydride particles.

[0028] The beneficial effects of the technical solution provided by the embodiment of the present application are:

[0029] The semi-solid lithium-ion battery provided in the embodiment of the present application comprises a positive electrode structure and a negative electrode structure, wherein the negative electrode structure comprises a current collector and a negative electrode active material layer and a solid electrolyte layer disposed on the current collector, and the solid electrolyte layer is disposed on the negative electrode active material layer. Since the current high-rate battery has a higher requirement for the thickness of the pole piece, after the solid electrolyte layer is disposed on the negative electrode active material layer, the thickness of the pole piece is too large, which is not conducive to the improvement of the battery rate performance. The present application covers a conductive layer on the surface of the current collector, and the conductive layer is obtained by applying a conductive slurry to the surface of the current collector through a carbon coating process. The current collector in the negative electrode structure is carbonized by the carbon coating process, and graphene with different particle sizes is used as a conductive agent to further improve the performance of the carbon coating layer; and a multi-layer negative electrode active material layer is arranged in the negative electrode structure, which not only avoids the problem of the negative electrode active material layer and the current collector layer falling off due to frequent large current charging and discharging, but also improves the rate performance of the battery, making it possible to arrange a solid electrolyte layer on the surface of the negative electrode active material in the rate type product to improve the safety performance, and a better solution to the contradiction between the safety and energy density of the rate battery is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 is a schematic structural diagram of the negative electrode structure of a semi-solid lithium-ion battery provided in an embodiment of the present application;

[0032] Figure 2 Schematic diagram of another structure of the negative electrode structure of the semi-solid lithium-ion battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] As described in the background technology, rate batteries require thinner negative electrode active material layers and binder content, which leads to a decrease in energy density. Therefore, for rate batteries, how to improve rate performance while further improving safety and energy density becomes very important. The applicant of this application has found through experiments that for rate batteries, frequent high-current charging and discharging easily leads to the shedding of the negative electrode active material layer and the current collector layer, affecting the overall safety performance of the battery.

[0035] In order to solve one or more of the above problems, the solution in the present application designs the negative electrode structure according to the characteristics of the rate battery, adopts the current collector carbon coating process, and sets a multi-layer negative electrode active material layer, which not only avoids the problem of easy detachment of the current collector, but also improves the energy density of the battery, so that the semi-solid lithium-ion battery in the present application has high rate, high energy density and high safety performance.

[0036] The solution provided by the embodiments of the present application is described in detail below with reference to the accompanying drawings.

[0037] Figure 1 is a schematic diagram of the negative electrode structure of the semi-solid lithium-ion battery provided in the embodiment of the present application, referring to Figure 1As shown, the semi-solid lithium-ion battery provided in the embodiment of the present application comprises at least a positive electrode structure and a negative electrode structure arranged relatively. Among them, the negative electrode structure comprises at least a current collector 1, a negative electrode active material layer 3 and a solid electrolyte layer 4, the negative electrode active material layer 3 and the solid electrolyte layer 4 are both arranged on the current collector 1, and the solid electrolyte layer 4 is arranged on the negative electrode active material layer 3, that is, the negative electrode active material layer 3 is arranged between the current collector 1 and the solid electrolyte layer 4. In order to solve the problem that frequent high-current charging and discharging of rate batteries easily leads to the shedding of the negative electrode active material layer and the current collector layer, the current collector used in the embodiment of the present application is treated with carbon coating. In specific implementation, the surface of the current collector is covered with a conductive layer 2, and the conductive layer 2 is obtained by applying a conductive slurry to the surface of the current collector through a carbon coating process.

[0038] The electrolyte composition of semi-solid lithium battery cells contains solid electrolyte components, and the liquid electrolyte content is significantly lower than the liquid electrolyte content of traditional liquid lithium-ion batteries.

[0039] As a preferred implementation mode, in the examples of the present application, without violating the inventive concept of the present application, any known current collector material can be used in the present application, including but not limited to copper foil.

[0040] As a preferred implementation, in the embodiment of the present application, the process of carbonizing the current collector includes:

[0041] S1. Preparation of carbon-coated slurry (ie, conductive slurry):

[0042] First, graphene powder and dispersant are dissolved in water to obtain a graphene dispersion. The graphene consists of two parts: graphene of a first particle size and graphene of a second particle size. The first particle size is larger than the second particle size. Specifically, the D50 of the graphene of the first particle size is 150-200nm, and the D50 of the graphene of the second particle size is 40-60nm. D50 is a common meaning in this field, representing the diameter of the powder particles, specifically indicating the diameter of the cumulative 50% point (or 50% passing particle size), which will not be repeated here.

[0043] Secondly, a preset mass of binder is added to the graphene dispersion, and mixed evenly in a high-speed mixer to obtain a conductive paste. In the obtained conductive paste, the mass ratio of graphene, dispersant, and binder is 4-9:0.5-1:1-2, respectively, wherein the mass of graphene, dispersant, and binder accounts for (10-12) wt% of the mass of the entire conductive paste, and the mass ratio of graphene with the first particle size to graphene with the second particle size is [20-30]:[70-80].

[0044] Specifically, the mass ratio of graphene in the conductive slurry can be 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt% or 9wt%, the mass ratio of the dispersant can be 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt%, 0.7wt%, 0.75wt%, 0.8wt%, 0.85wt%, 0.9wt%, 0.95wt% or 1wt%, and the mass ratio of the binder can be 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2wt%. S2. Slurry coating:

[0045] The graphene slurry (ie, conductive slurry) prepared in the above steps is coated on a current collector, which includes but is not limited to copper foil. Preferably, the single-layer coating surface density of the conductive slurry coated on the surface of the current collector is 1.11 to 1.95 g / ㎡.

[0046] S3, heat-treating the current collector after coating the slurry to obtain a final conductive layer. Preferably, the temperature of heat-treating the current collector after coating the slurry is 450-500° C. Preferably, the thickness of the final conductive layer is 1.5-2.5 μm.

[0047] Specifically, the thickness of the conductive layer may be 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm or 2.5 μm.

[0048] Although it is known to coat the surface of the current collector with a conductive layer, for example, conventional conductive materials such as graphite are used. However, conventional conductive layers are thick, weak, and have low bonding strength with the negative electrode active material layer. Surprisingly, graphene conductive coatings can effectively overcome the above defects, which is only a guess rather than any limitation on the scope of protection. The highly layered structure of graphene is conducive to the extension and flattening of the conductive layer in the horizontal direction, which further reduces the thickness of the conductive coating.

[0049] At the same time, the use of graphene with different particle sizes can achieve a "large" size effect. Graphene with large particles plays a skeletal support role for the entire conductive coating, and graphite with small particles can reinforce areas of the conductive coating that large-particle graphene cannot reach. The two specific types of graphene sizes improve the overall performance of the conductive coating.

[0050] As a preferred implementation, in the embodiment of the present application, the negative electrode active material layer includes a binder, a conductive agent and a negative electrode active material. It should be noted that the negative electrode active material, the binder and the conductive agent are not particularly limited in the embodiment of the present application, and the user can select them according to actual needs.

[0051] In one embodiment, the negative electrode structure may include a carbonaceous-based negative electrode active material including any one or a combination of at least two of graphite, graphene, or carbon nanotubes (CNTs).

[0052] Preferably, the negative electrode active material is artificial graphite.

[0053] In one embodiment, the negative electrode active material in the negative electrode structure can be doped with one or more conductive materials that provide an electronic conduction path and / or at least one polymer binder material that improves the structural integrity of the negative electrode. For example, the negative electrode active material can be doped with a binder such as poly(tetrafluoroethylene) (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, and combinations thereof.

[0054] Conductive agents may include carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include particles such as carbon black, graphite, superP, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate, etc.

[0055] The negative electrode structure may also include a solid electrolyte material. The addition of the solid electrolyte material is conducive to improving the overall ionic conductivity of the negative electrode sheet. The solid electrolyte particles may include one or more polymer components, oxide particles, sulfide particles, halide particles, borate particles, nitride particles or hydride particles. When polymer particles are used, lithium salts may be used for compounding.

[0056] As a preferred embodiment, in the embodiment of the present application, the thickness of the negative electrode active material layer is 5-300 μm, preferably, the thickness of the negative electrode active material layer is 10-200 μm, and more preferably, the thickness of the negative electrode active material layer is 20-50 μm. For example, the thickness of the negative electrode active material layer is 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc.

[0057] The thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer may be 1:0.2-5.

[0058] Since the same negative electrode active material is used, there is no special limitation on the thickness of the first negative electrode active material layer and the second negative electrode active material layer. When the thickness of the first negative electrode active material layer is larger, the bonding strength between the entire negative electrode active material layer and the current collector is greater. When the thickness of the second negative electrode active material layer is larger, the energy density of the material system is higher.

[0059] As a preferred embodiment, the negative electrode active material layer adopts a multi-layer structure, that is, the negative electrode active material layer includes two or more layers. Figure 2 is another schematic diagram of the negative electrode structure of the semi-solid lithium-ion battery provided in the embodiment of the present application, referring to Figure 2 As shown, as a preferred implementation, in the embodiment of the present application, the negative electrode active material layer includes at least a first negative electrode active material layer 3′ and a second negative electrode active material layer 3″, wherein the first negative electrode active material layer 3′ is arranged on a side close to the current collector 1, and the second negative electrode active material layer 3″ is arranged on a side close to the solid electrolyte layer 4.

[0060] Preferably, the binding force of the binder of the negative electrode active material layer (i.e., the first negative electrode active material layer) close to the current collector 1 is stronger than that of the negative electrode active material layer (i.e., the second negative electrode active material layer) close to the solid electrolyte side. In this way, on the one hand, the advantage of the higher binding property of the binder in the first negative electrode active material layer is used to ensure that the negative electrode sheet has excellent peel strength, and on the other hand, the problem of product cracking can be avoided by using the lower binding property of the binder in the second negative electrode active material layer.

[0061] Further preferably, the content of the binder in the negative electrode active material layer close to the solid electrolyte side (ie, the second negative electrode active material layer) is lower than the content of the binder in the negative electrode active material layer close to the current collector side (ie, the first negative electrode active material layer).

[0062] Preferably, the content of the binder in the first negative electrode active material layer is 2.5-3wt%, the content of the binder in the second negative electrode active material layer is 1.5-2.5wt% and the total content of the binder in the first negative electrode active material layer and the second negative electrode active material layer meets 1.6-2.5%.

[0063] Specifically, the content of the binder in the first negative electrode active material layer may be 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 1.9wt% or 2wt%, and the content of the binder in the second negative electrode active material layer may be 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt% or 2.5wt%.

[0064] As a preferred embodiment, in the embodiment of the present application, a solid electrolyte layer is provided on the surface of the negative electrode active material layer. The solid electrolyte layer may be LLZO or LLTO. The thickness of the solid electrolyte layer is 1-10 μm, preferably, the thickness of the solid electrolyte layer is 2-5 μm. The binder content in the solid electrolyte layer is 1-2 wt%.

[0065] Setting up a solid electrolyte layer can further improve the safety performance of the battery.

[0066] The present application does not specifically limit the type of solid electrolyte material, and any known solid electrolyte material can be used in the present application, and the solid electrolyte material in the solid electrolyte layer and the solid electrolyte material in the electrode can independently select the same or different materials.

[0067] Specifically, the binder content in the solid electrolyte layer may be 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt% or 2 wt%.

[0068] Example 1

[0069] A semi-solid lithium-ion battery is provided in an embodiment of the present application, the battery comprising a positive electrode structure and a negative electrode structure, the negative electrode structure comprising a current collector and a negative electrode active material layer and a solid electrolyte layer arranged on the current collector, and the solid electrolyte layer is arranged on the negative electrode active material layer, the surface of the current collector is covered with a conductive layer, the conductive layer is obtained by applying a conductive slurry to the surface of the current collector through a carbon coating process, and the negative electrode active material layer comprises a first negative electrode active material layer.

[0070] The process of carbonization of the current collector can be referred to above and will not be described here one by one. The graphene in the conductive paste is composed of 20wt% of graphene with a first particle size of 180nm and 80wt% of graphene with a second particle size of 50nm. The mass ratios of graphene, dispersant and binder in the conductive paste are 8wt%, 1wt% and 1.5wt% respectively.

[0071] The first negative electrode active material layer is composed of 95wt% graphite, 2wt% PVDF and 3wt% super-P, and the solid electrolyte layer is composed of 98wt% LLTO and 2wt% PTFE.

[0072] Example 2

[0073] The difference from Example 1 is that the graphene in the conductive paste consists of 50 wt % of graphene with a first particle size of 180 nm and D50 and 50 wt % of graphene with a second particle size of 50 nm.

[0074] Example 3

[0075] The difference from Example 1 is that the graphene in the conductive paste consists of 80 wt % of graphene with a first particle size of 180 nm and D50 and 20 wt % of graphene with a second particle size of 50 nm.

[0076] Example 4

[0077] The difference from Example 1 is that the graphene in the conductive paste consists of 100 wt % of graphene with a first particle size of 180 nm and a D50.

[0078] Example 5

[0079] The difference from Example 1 is that the graphene in the conductive paste consists of 100 wt % of graphene with a second particle size of 50 nm and a D50.

[0080] Example 6

[0081] The difference from Example 1 is that the negative electrode active material layer includes at least a first negative electrode active material layer close to the current collector side and a second negative electrode active material layer close to the solid electrolyte layer, the first negative electrode active material layer is composed of 94.5wt% of graphite, 2.5wt% of PVDF and 3wt% of super-P, and the second negative electrode active material layer is composed of 95.5wt% of graphite, 1.5wt% of PVDF and 3wt% of super-P.

[0082] Example 7

[0083] The difference from Example 6 is that the second negative electrode active material layer consists of 95.5 wt % of graphite, 1.5 wt % of PEO and 3 wt % of super-P.

[0084] Test method:

[0085] 1. Acupuncture test:

[0086] S101, fully charge using standard charging method;

[0087] S102, use a φ5mm~φ8mm high temperature resistant steel needle (the cone angle of the needle tip is 45°~60°, the surface of the needle is smooth, free of rust, oxide layer and oil), penetrate the battery cell plate in a direction perpendicular to the battery cell plate at a speed of (25±5)mm / s, the penetration position should be close to the geometric center of the pierced surface, and the steel needle stays in the battery cell;

[0088] S103. Observe for 1 hour.

[0089] Record battery safety level

[0090] 2. Room temperature 3C rate discharge performance

[0091] At room temperature, charge at 1C to the termination voltage, with a cutoff current of 0.05C, let stand for 30 minutes, and discharge at 1C and 3C to the termination voltage respectively. Record the discharge capacity and compare the 3C discharge capacity with the 1C discharge capacity to obtain the room temperature 3C rate discharge performance.

[0092] 3. Capacity retention rate after 500 cycles at room temperature

[0093] S201, charge at 1C or specified current to the termination voltage, cut-off current 0.05C, and let stand for 30 minutes;

[0094] S202, discharge at 1C to the final discharge voltage, record the discharge capacity, and let stand for 30 minutes;

[0095] Cycle S201-S202;

[0096] The test results are as follows:

[0097] acupuncture 3C rate performance Cycle performance Example 1 pass 96.4% 97.1% Example 2 pass 92.6% 92.5% Example 3 pass 94.1% 93.7% Example 4 pass 91.9% 91.5% Example 5 pass 93.2% 92.6% Example 6 pass 97.9% 97.5% Example 7 pass 98.5% 98.3%

[0098] It can be seen from the test results that the semi-solid lithium-ion batteries provided in the present application have improved safety due to the provision of a solid electrolyte layer, and all of them have passed the puncture test. In addition, the graphene conductive coating with a specific ratio in Example 1 has the best performance, indicating that adjusting the ratio of graphene with different particle sizes can effectively improve product performance. Two layers of negative electrode active material layers are provided, and the content and type of the binder are adjusted through the use of the inner and outer layers of the negative electrode active material layers, which further improves the battery performance, and the 3C rate performance and cycle performance are excellent.

[0099] In the description of the present application, it should be understood that the terms "vertical", "parallel", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present application, unless otherwise specified, "multiple" means two or more.

[0100] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0101] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A semi-solid lithium-ion battery, characterized in that: The battery comprises a positive electrode structure and a negative electrode structure, wherein the negative electrode structure comprises a current collector and a negative electrode active material layer and a solid electrolyte layer disposed on the current collector, wherein the solid electrolyte layer is disposed on the negative electrode active material layer, and the surface of the current collector is covered with a conductive layer, wherein the conductive layer is obtained by applying a conductive slurry to the surface of the current collector through a carbon coating process, and the conductive material in the conductive slurry comprises graphene; The preparation process of the conductive paste includes: 1) dissolving graphene powder and a dispersant in a preset solvent to obtain a graphene dispersion, wherein the graphene includes at least two different particle sizes; 2) adding a preset amount of binder into the graphene dispersion and mixing the mixture evenly in a high-speed mixer to obtain the conductive slurry; The graphene includes graphene of a first particle size and graphene of a second particle size, the D50 of the graphene of the first particle size is 150-200nm, and the D50 of the graphene of the second particle size is 40-60nm; the mass ratio of the graphene of the first particle size to the graphene of the second particle size is [20-30]:[70-80]; the mass ratios of the graphene, the dispersant and the binder in the conductive paste are 4-9wt%, 0.5-1wt% and 1-2wt% respectively.

2. The semi-solid lithium-ion battery according to claim 1, characterized in that: The single-layer coating density of the conductive paste coated on the surface of the current collector is 1.11 to 1.95 g / ㎡.

3. The semi-solid lithium ion battery according to claim 1, characterized in that: The thickness of the conductive layer is 1.5-2.5 μm.

4. The semi-solid lithium-ion battery according to claim 1, characterized in that: The thickness of the negative electrode active material layer is 5-300 μm.

5. The semi-solid lithium ion battery according to claim 4, characterized in that: The thickness of the negative electrode active material layer is 10-200 μm.

6. The semi-solid lithium ion battery according to claim 5, characterized in that: The thickness of the negative electrode active material layer is 20-50 μm.

7. The semi-solid lithium-ion battery according to claim 1, characterized in that: The negative electrode active material layer includes at least a first negative electrode active material layer close to the current collector and a second negative electrode active material layer close to the solid electrolyte layer, and the binding force of the binder contained in the first negative electrode active material layer is stronger than the binding force of the binder contained in the second negative electrode active material layer.

8. The semi-solid lithium-ion battery according to claim 1, characterized in that: The solid electrolyte layer includes LLZO or LLTO.

Citation Information

Patent Citations

  • Lithium ion battery negative pole piece, production method thereof, and lithium ion battery

    CN105870400A

  • Negative pole piece as well as preparation method and application thereof

    CN113363419A